Dental caries: a review - Veiga, Nélio Jorge (2016)
ntroduction: Dental caries is the most prevalent chronic disease worldwide. It’s an infectious disease characterized by a multifactorial etiology and slow evolution that leads to the destruction of dental hard tissues. The implementation of preventive measures, the need of investing in education for the correct maintenance measures of oral health, associated with preventive and continuos medical and dental care, are key to the awareness of populations of its existence and to the decline of its prevalence. Throughout this article we intend to review some important aspects about dental caries and the main etiological factors envolved so that health professionals can intervene in the treatment and prevention of diseases. Materials and Methods: To carry out this review article the search strategies included electronic databases, such as Pubmed, Cochrane Library and Science Direct, reference lists of articles, and selected textbooks. Articles and textbooks used in this study were mainly reached by using the following keywords: “oral health”, “dental caries”, “etiological factors”, “risk factors”, “primary dental prevention”. Selection criteria included articles published from 1990 to the present year of 2016 that described the definition, etiology and other characteristics associated with the disease dental caries. At the end of the search, 16 scientific articles were selected. Results: Dental caries is a disease that develops through gradual complex biological interactions of acidogenic bacteria, fermentable carbohydrates and host factors such as the teeth and saliva, during time. The disease developes due to multifactorial aspects, since biological to social aspects that the oral health professional should be aware of. Discussion: The implementation of preventive measures, the need of investing in education for the correct maintenance measures of oral health, associated with preventive and continuos medical and dental care, are key for the awareness of populations of its existence and contribute for the decrease of the prevalence of oral diseases. Conclusions: Dental caries should be seen as a fairly common condition that can greatly affect the health and quality of life of patients, so it is extremely important to increase the knowledge towards their mechanisms, focusing on prevention and the correct therapeutic approach. However, it is necessary to be aware of the hard work ahead in the future related with education and oral health promotion.